THE PERCEPTION OF ADOPTING AN INFORMATION TECHNOLOGY INNOVATION ON THE RURAL BANKS OWNED BY LOCAL GOVERNMENT (Proceeding Fakultas Ekonomi, 2013)
The performance of rural banks owned by the local government showed progress very proud. Therefore, policies and strategies for the future development of rural banks directed inaccordance with the fundamental characteristics of rural banks, which is rural banks as community banks are healthy, strong, productive and spread throughout Indonesia andfocused in the provision of financial services the small, micro and medium Enterprises (SME’s) and local communities, especially in rural areas. The purpose of this study was to find out which variables are to be determinant to measure the user’s perceptions of adopting an information technology (IT) innovation on the rural banks owned by local government. Respondents in this study were employees as user’sadoption of IT on rural banks. Data obtained from respondents' answers to the questionnaire. The factors that influence adopting an information technology innovation, which isvoluntariness, relative advantage, compatibility, image, ease of use, result demonstrability, visibility, trial ability, and facilitating conditions to be determined by principle componentanalysis under Factor Analysis Techniques. The adoption of information technologies by individuals and organizations has been an area of substantial research to extend information system. One of the important strategiesthat need to be done by the rural banks in order to increase competitiveness and outreach is empowering of supporting infrastructure industries owned by rural banks effectively, especially in information technology.Keywords: information system, technology innovation, principle component